2003
DOI: 10.1111/j.1349-7006.2003.tb01395.x
|View full text |Cite
|
Sign up to set email alerts
|

Tumor hypoxia: A target for selective cancer therapy

Abstract: Tumor hypoxia has been considered to be a potential therapeutic problem because it renders solid tumors more resistant to sparsely ionizing radiation (IR) and chemotherapeutic drugs. Moreover, recent laboratory and clinical data have shown that tumor hypoxia is also associated with a more malignant phenotype and poor survival in patients suffering from various solid tumors. Therefore, selective targeting of hypoxic tumor cells has been explored, and since severe hypoxia (pO 2 < < < <0.33%, 2.5 mmHg) does not o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
260
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 329 publications
(272 citation statements)
references
References 45 publications
3
260
0
3
Order By: Relevance
“…It is also well known that hypoxia enhances the proliferation of cancer cells 45,46) . HIF-1α is one of the key molecules contributing to cancer progression [46][47][48] , making it a target molecule for cancer therapies 47,48) . Induction of HIF-1α protein is required for the growth enhancement hypoxic cells 22,[46][47][48] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also well known that hypoxia enhances the proliferation of cancer cells 45,46) . HIF-1α is one of the key molecules contributing to cancer progression [46][47][48] , making it a target molecule for cancer therapies 47,48) . Induction of HIF-1α protein is required for the growth enhancement hypoxic cells 22,[46][47][48] .…”
Section: Discussionmentioning
confidence: 99%
“…HIF-1α is one of the key molecules contributing to cancer progression [46][47][48] , making it a target molecule for cancer therapies 47,48) . Induction of HIF-1α protein is required for the growth enhancement hypoxic cells 22,[46][47][48] . In C2C12 cells, HIF-1α protein was induced by myogenic induction in the present study, in agreement with previous reports 26,49) .…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia is considered to be a potential barrier for treating tumors because it induces the development of cell clones with an aggressive and treatment-resistant phenotype, which leads to rapid progression and poor prognosis (Kizaka-Kondoh et al, 2003;Vaupel, 2008). It has been shown that hypoxia can decrease the therapeutic efficacy of radiation treatment, surgery, and some forms of chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…In order to eradicate HIF-1a-expressing hypoxic cells, we have developed TOP3 (TAT-ODD-procaspase-3), a fusion protein with three domains (Figure 1) (Harada et al, 2002(Harada et al, , 2005(Harada et al, , 2006Kizaka-Kondoh et al, 2003;Inoue et al, 2004). The PTD is derived from the protein-transduction domain (PTD) of the human immunodeficiency virus type-1 tat protein (Schwarze et al, 1999) and efficiently delivers TOP3 to any tissue in vivo.…”
Section: Introductionmentioning
confidence: 99%